Are verbs politically correct? A corpus study of gender in Russian verbs - Kuznetsova, Julia (Gender and Language, 2015)
In Russian, the past tense form of a verb contains a gender marker agreeing with the subject. This gives us a unique opportunity to explore the verbs’ distribution by gender, using the relation between forms with feminine and masculine endings as the basis for a fem:masc ratio. The present study shows that an average Russian verb in the Russian National Corpus has three masculine past tense forms for each feminine past tense form. This article explores verbs at the two extremes of the fem:masc scale: the top 100 primarily masculine verbs and the top 100 primarily feminine verbs. These groups of verbs provide a concrete basis for assessing cultural stereotypes associated with gender.